Long-term oncologic outcomes following breast cancer surgery in adolescents and young adults: a single-center retrospective analysis - Liu, Xin; Ma, Zengyan; Chu, Hongwu; Nie, Weihong; Sun, Guoxin; Zhao, Kaihua; Zou, Xiao (Frontiers in Oncology, 2024)
Background: Breast cancer (BC) in adolescents and young adults (AYAs, aged 15-39 years), remains inadequately understood. The incidence of BC in AYAs has been steadily increasing, making it the second leading cause of cancer-related mortality among females aged 0-39 globally. This study aimed to elucidate the clinical characteristics and long-term outcomes of AYAs and older adults (OAs, aged > 39 years) with BC who underwent surgery.Methods: From January 2011 to June 2017, BC patients who underwent surgery were enrolled in this study and divided into AYA group and OA group. Clinical characteristics, recurrence-free survival (RFS), and overall survival (OS) were compared between these two groups, both before and after propensity score matching (PSM). Univariate and multivariate Cox proportional hazard regression analyses were performed to assess the influence of age on OS and RFS.Results: Compared to the OA group, the AYA group exhibited a younger age at menarche (p < 0.001), a lower prevalence of menopausal status (p < 0.001), a reduced occurrence of comorbid conditions (p < 0.001), fewer instances of undergoing mastectomy (p = 0.031), a higher incidence of Triple-Negative Breast Cancer (TNBC) (p = 0.046), and elevated Ki-67 levels (p = 0.036). In terms of prognostic outcomes, within the study cohort, AYAs had a higher mortality rate and poorer longterm survival compared to OAs, both before and after PSM. In the PSM cohort, AYAs experienced a significantly shorter median OS (p < 0.001) and RFS (p < 0.001). Young age (15-39 years) emerged as an independent risk factor for OS (HR 2.659, 95% CI 1.385-5.106, p = 0.003) and RFS (HR 3.235, 95% CI 2.085-5.022, p < 0.001) in BC patients following surgery.Significant differences were identified in the clinicopathological characteristics between AYA and OA patients with BC. In comparison to OA patients, AYA patients exhibited a less favorable long-term prognosis, with young age emerging as an independent prognostic risk factor for both OS and RFS in BC patients following surgery. Further investigations are warranted to develop age-specific therapeutic approaches for AYA BC patients.